Associations of extracurricular activity participation with bullying victimization among U.S. middle and high school students: A nationally representative sample. (2nd October 2022) - Sheridan, Steven; Clary, Laura K.; Webb, Lindsey; Stuart, Elizabeth A.; Mendelson, Tamar
ABSTRACT: While prior studies have addressed bullying experienced during school, limited research exists on the associations between participation in school-sponsored extracurricular activities and bullying victimization risk. The current study utilized data from the 2013, 2015, and 2017 National Crime and Victimization Survey's School Crime Supplement (n = 13, 376) to examine the associations between participation in different types of extracurricular activities and three types of bullying victimization (physical, verbal, and relational) among middle and high school students. Results indicated that participation in performing arts, service clubs, and "other" activities was associated with all three types of victimization. Additionally, participation in athletics was associated with decreased risk for verbal victimization. Prevention strategies and implications for schools regarding how to reduce bullying among middle and high school students, especially in the context of extracurricular activities, are discussed.